Comprometimento organizacional: um estudo empírico na indústria de TIC do Estado do Ceará - Lima, João Gabriel Carneiro Costa (2019)
With the strengthening of the behavioral approach of people management from the 1960s, a new field of multidisciplinary study called organizational behavior emerged. This field studies the behavior of people within an organization and its impact on performance. One of the most important manifestations of an individual's behavior in the organization to which he belongs is the established links between him and the organization. Among the links, the commitment is highlighted. It is in this context that the research seeks to apply the model of organizational commitment of Medeiros (2003) that initially presents itself as a scale of organizational commitment with good adjustment to the Brazilian culture. The model of Medeiros (2003) is composed by four dimensions: affective (identification with the values and objectives of the organization), affiliative (feeling of being part of the group), normative (the individual commits himself to the organization because he thinks it is right morally to do) and continuance (impairment resulting from the calculation of costs and benefits associated with their stay in the company). The research was applied with workers from the Information and Communication Technology (ICT) industry in the brazilian state of Ceará. The choice for this group is justified by the high turnover rate of the sector, its large contingent of young professionals, and its positive impact on the dynamics of other sectors. The research is classified as quantitative, descriptive (since it seeks to discover the characteristics of a given population or phenomenon) and explanatory, because it seeks to discover which factors (sociodemographic variables) contribute to the occurrence of a phenomenon (organizational impairment). A total of 385 (three hundred eighty-five) responses were collected through a questionnaire composed of seven sociodemographic variables (gender, marital status, employment status, occupational group, family financial responsibility, education level and length of service) and 30 (thirty) questions from the Medeiros model (2003). The techniques of Analysis of Variance (ANOVA) and Confirmatory Factor Analysis (CFA) were applied with the aid of SPPS and AMOS software. The results indicate that the model of Medeiros (2003) does not fit well with the group studied (workers from the ICT industry in Ceará), and it is possible to arrive at the model of good fit with three dimensions: affective-affiliative (gathers affective and affiliative), normative and continuance. Another important conclusion was the considerable lower level of instrumental and affective-affiliative commitment among outsourcers.